1992
DOI: 10.1104/pp.100.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acid Efflux as a Mechanism of Hypoxic Acclimation of Maize Root Tips to Anoxia

Abstract: Hypoxic pretreatment (3 kPa oxygen) of maize (Zea mays L.) root tips improved their survival time in a subsequent anoxic incubation from 10 h to more than 3 d, provided that glucose was added to the medium to sustain metabolism. The glycolytic flux (lactate + ethanol) was the same in both pretreated and untreated root tips during the 1st h after transfer to anoxia. It was only after 2 h that it declined sharply in untreated tips, but was sustained in pretreated ones. Right after the transition from normoxia to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
83
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 32 publications
(64 reference statements)
7
83
1
Order By: Relevance
“…The gating of this channel appears to be directly regulated by external Al concentration, is cell-specific and is under the control of a single gene (Kochian, 1995). Similar mechanisms have been proposed for lactate efflux under anaerobiosis, and organic acid efflux under P and Fe deficiency (Hoffland, 1992 ;Xia & Saglio, 1992 ;Xia & Roberts, 1994).…”
Section: Hypothesis 3 Root Carbon Acquisition Is Controlled By Demanmentioning
confidence: 85%
“…The gating of this channel appears to be directly regulated by external Al concentration, is cell-specific and is under the control of a single gene (Kochian, 1995). Similar mechanisms have been proposed for lactate efflux under anaerobiosis, and organic acid efflux under P and Fe deficiency (Hoffland, 1992 ;Xia & Saglio, 1992 ;Xia & Roberts, 1994).…”
Section: Hypothesis 3 Root Carbon Acquisition Is Controlled By Demanmentioning
confidence: 85%
“…The extent of cytoplasmic acidification in plants under low oxygen has been shown to correlate with their intolerance of stress (Xia and Roberts, 1996). Xia and Saglio (1992) found that hypoxia-acclimated maize root tips have a higher cytoplasmic pH under anoxia than in the case of non-acclimated maize root tips. In addition, the acidification of cell sap has been induced by anoxia in non-resistant plants like wheat and barley.…”
Section: Resultsmentioning
confidence: 99%
“…2), ADH was not likely to be the factor that limited ethanol production. Xia and Saglio (1992) also suggested that the activity of ADH was not the limiting factor for the accumulation of ethanol in some plant tissues. On the other hand, PDC was reported to be an allosteric enzyme, as indicated by the sigmoidal relationship between activity and pyruvate concentrations (Rivoal et al, 1990).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anoxic conditions showed no considerable effect on ADH and LDH activity. A direct involvement of ADH and LDH in the resistance of maize plants to anoxia has not been confirmed (Xia & Saglio, 1992).…”
Section: Resultsmentioning
confidence: 99%